A Classroom Simulation of the Syrian Conflict. Issue 4 (October 2019) - Frank, Richard W.; Genauer, Jessica
ABSTRACT: This article describes a semester-long classroom simulation of the Syrian conflict designed for an introductory international relations (IR) course. The simulation culminates with two weeks of multi-stakeholder negotiations addressing four issues: humanitarian aid, economic sanctions, ceasefire, and political transition. Students randomly play one of 15 roles involving three actor types: states, non-state actors, and international organizations. This article outlines the costs and benefits of simulation design options toward encouraging students' understanding of IR concepts, and it proposes a course plan for tightly integrating lectures, readings, assessment, and simulation—regardless of class size or length. We highlight this integration through a discussion of two weeks' worth of material—domestic politics and war, and non-state actors—and the incorporation of bargaining concepts and frameworks into the two weeks of simulated multi-stakeholder negotiations.